Modelling of the surface of the liquid metal drop with nonfixed radius - Čiupaila, Regimantas (Lietuvos matematikos rinkinys, 2005)
Two first order nonlinear differential equations system with the separated boundary conditions and nonlocal integral conditions is considered. The system is modeling the surface of the liquid micro volume drop with nonfixed radius on the horizontal plane. The boundary problem is brought to the initial one. The iterative algorithm is proposed to count the curve of the crest of the drop depending on some geometrical and mechanical parameters.